Study on Late Childhood Students: Psychological Intelligence and Fundamental Motor Skills as Predictors of Physical Fitness - Sugi Fadilah; Indra Safari; Aam Ali Rahman (Universitas Tadulako, 2026)
The physical fitness level of elementary school students is a complex outcome, which depends on psychological preparation and motor skills. The purpose of this study was to evaluate the hypothesis about the psychological intelligence of 11-year-old elementary school children using multiple linear regression analysis. The study sample consisted of 71 students (37% boys and 63% girls) recruited through a purposive sampling procedure. The measurements used were the psychological intelligence questionnaire, the Gross Motor Development Test-3 (TGMD-3), and the Indonesian Physical Fitness Test (TKJI). Before testing the hypothesis, checking the classical assumptions showed that the residual data had a normal distribution (P = 0.200), were not multicollinear (VIF = 1.050), and were homoscedastic (Glejser test). The results of the multiple regression analysis showed that psychological intelligence and basic motor skills significantly influenced the level of physical fitness simultaneously, F = 28.042 (P = 0.000 < 0.05). Partially, the most prominent positive predictor was basic motor skills (t = 5.397, P = 0.000), indicating that high-quality movement competence significantly increases active physical engagement in children. In addition, psychological intelligence also had a significant partial positive effect on physical fitness with a t value of 2.983 (P = 0.004), proving that emotional self-regulation and stress management as important internal drivers help prevent psychological anxiety and maintain physiological resilience during strenuous testing. In conclusion, improving adolescent fitness configuration requires a paradigm shift towards a comprehensive Physical Literacy approach.